2004
DOI: 10.1021/cm048667y
|View full text |Cite
|
Sign up to set email alerts
|

New Ways to High-Quality Bulk Scandium Nitride

Abstract: ScN was prepared in three different ways leading to single phase samples with low oxygen content in a broad range of particle sizes. Synthesis from the elements provides, in an exothermic reaction, brownish transparent single crystals (rock-salt structure type, space group Fm3 hm, a ) 451.2(1) pm, Z ) 4, R int ) 0.034, R1 ) 0.013, wR2 ) 0.018). From a decomposition reaction of Li 3 [ScN 2 ] fine brown powders (particle size ≈ 1 µm) were obtained. Via nitridation of intermetallic Sc-In phases even nanoscaled (<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
(35 reference statements)
2
18
0
1
Order By: Relevance
“…The mass density deduced from the X-ray reflectivity measurements varies from 3.75(1) g cm -3 at low temperature to 4.09 (1) g cm -3 at high temperature. The densities obtained can be compared to the ScN bulk values of 4.25(2) [39]. The film deposited on c-plane Al2O3 do not exhibit a clear difference of the cell parameter when the TD increases from 700 C to 950 C with a value close to 4.504(4) Å.…”
Section: Resultsmentioning
confidence: 92%
“…The mass density deduced from the X-ray reflectivity measurements varies from 3.75(1) g cm -3 at low temperature to 4.09 (1) g cm -3 at high temperature. The densities obtained can be compared to the ScN bulk values of 4.25(2) [39]. The film deposited on c-plane Al2O3 do not exhibit a clear difference of the cell parameter when the TD increases from 700 C to 950 C with a value close to 4.504(4) Å.…”
Section: Resultsmentioning
confidence: 92%
“…Figure shows the SEM images of the ScN crystals grown at different temperatures for the case of 10 at.% Sc concentration. Unlike the cuboid shape of the crystals prepared by the direct reaction of element Sc and N 2 , all of the crystals grown from indium flux exhibited a rounded shape which may arise from a high supersaturation of the solution. Based on the SEM images in Fig.…”
Section: Resultsmentioning
confidence: 86%
“…On the other hand, ScN particles have been also synthesized. Several authors have reported about the direct reaction of Sc metal with N 2 gas at high temperatures (1007–2060°C), resulting in several hundred micrometer‐sized gray–black or blue crystals. Niewa et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For (Sc 3 N)In the transition from the hexagonal binary intermetallic compound to the cubic perovskite indicates a structure determining effect of the nitride ion, as discussed in more detail for the reversible case of related perovskite hydrides . All compounds ( R 3 N)In readily react with excess N 2 at elevated temperatures forming the binary rare‐earth metal nitride R N and In metal …”
Section: Inverse Perovskite Nitrides Of the Rare‐earth Metalsmentioning
confidence: 98%